Beggar-thy-neighbor or favor thy industry? An empirical review of transatlantic tariff retaliation - Martin Braml (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Since 2018, the U.S. and the EU have been erecting additional tariff barriers against each other. This study takes stock of existing transatlantic retaliatory tariffs and examines three different motives that explain how products are chosen to qualify for tariff retaliation. These channels are: shifting the tariff incidence abroad according to optimal tariff theory, concentrating losses abroad in politically sensitive regions or industries, and rent-seeking by domestic lobbyists. I find striking evidence for the presence of all three channels. Moreover, this study performs an ex-post impact evaluation of EU tariffs implemented in response to U.S. steel and aluminum tariffs: within one year, imports of treated products from the U.S. fell by 36 percent. Trade diversion can only partially offset this decline in imports. Finally, this study outlines a concept for a transparent protocol which could be applied to the selection of products for retaliation purposes.
Keywords: F13; F14; F53; 330; retaliatory tariffs; countervailing duties; optimal tariff theory; Beggar-thy-Neighbor; EU-US trade; GATT